Auxin Modulated Initiation of Lateral Roots Is Linked to Pericycle Cell Length in Maize - Alarcón, M. Victoria; Salguero, Julio; Lloret, Pedro G. (Frontiers in Plant Science, 2019)
Auxin is essential for the regulation of root system architecture by controlling primary root elongation and lateral root (LR) formation. Exogenous auxin has been reported to inhibit primary root elongation and promote the formation of LRs. In this study, LR formation in the Zea mays primary root was quantitatively evaluated after exogenous auxin treatment by comparing the effects of auxin on two selected zones elongated either before or after auxin application. We determined two main variables in both zones: the LR density per unit of root length (LRD), and the mean phloem pericycle cell length. The total number of phloem pericycle cells (PPCs) per unit of root length was then calculated. Considering that each LR primordium is initiated from four founder cells (FCs), the percentage of PPCs (%PPC) that behave as FCs in a specific root zone was estimated by dividing the number of pericycle cells by four times the LRD. This index was utilized to describe LR initiation. Root zones elongated in the presence of a synthetic auxin (1-naphthalene acetic acid, NAA) at low concentrations (0.01 μM) showed reduced cell length and increased LRD. However, a high concentration of NAA (0.1 μM) strongly reduced both cell length and LRD. In contrast, both low and high levels of NAA stimulated LRD in zones elongated before auxin application. Analysis of the percentage of FCs in the phloem pericycle in zones elongated in the presence or absence of NAA showed that low concentrations of NAA increased the %PFC, indicating that LR initiation is promoted at new sites; however, high concentrations of NAA elicited a considerable reduction in this variable in zones developed in the presence of auxin. As these zones are composed of short pericycle cells, we propose that short pericycle cells are incapable to participate in LR primordium initiation and that auxin modulated initiation of LRs is linked to pericycle cell length.